2001
DOI: 10.1046/j.1439-0396.2001.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant oils and aspartate on rumen fermentation in vitro

Abstract: The effect of plant oils and aspartate (ASP) on rumen fermentation in vitro. The objective of this study was to determine the effect of plant oils (rapeseed - RO, sunflower - SO; linseed - LO; 10% wt/wt) and 8 mmol sodium aspartate on rumen fermentation of a diet (250 mg) consisting of hay, barley and sugar beet molasses (60 : 30 : 10). Rumen fluid was collected from two Slovak Merino sheep fed the same diet twice daily. Mixed ruminal micro-organisms were incubated in fermentation fluid (40 ml) containing rume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
1
18
1
Order By: Relevance
“…According to Jalc and Ceresnakova (2002), if the addition of dietary fat interferes with normal fibre digestion in the rumen, then butyrate and acetate will always be reduced. The general recommendation is that total dietary fat should not exceed 6-7% of dietary DM, otherwise an adverse effect on rumen fermentation could be observed (Jenkins 1993).…”
Section: Discussionmentioning
confidence: 99%
“…According to Jalc and Ceresnakova (2002), if the addition of dietary fat interferes with normal fibre digestion in the rumen, then butyrate and acetate will always be reduced. The general recommendation is that total dietary fat should not exceed 6-7% of dietary DM, otherwise an adverse effect on rumen fermentation could be observed (Jenkins 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that if added dietary fat interferes with normal fibre digestion in the rumen, butyrate and acetate will always be reduced (Jalč and Čerešňáková, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…There are many conflicting data concerning ammonia concentrations when the diet is supplemented with fats: some of the data show no effect of supplemented fats on ammonia concentrations (Jalč et al, 2005), while other publications reported increases (Jalč et al, 2002) or decreases (Doreau et al, 1991) following such supplementations. No statistically significant changes were observed in the ammonia concentration in any of our three experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies conducted by Mohammed et al (2004) demonstrated that addition of fumarate increased propionate production and reduced methane output. Malate has a similar effect (Jalc and Ceresnakova 2002). In vivo studies also demonstrated the potential effects of dicarboxylic acids on methane output (Bayaru et al 2001).…”
Section: Dicarboxylic Acidsmentioning
confidence: 92%